Implementasi PPDB Zonasi dalam Perspektif Teori Perubahan Kurt Lewin - Richard Leonando Aoetpah; Bambang Ismanto; Wasitohadi Wasitohadi (Universitas Indraprasta PGRI Jakarta, 2022)
New Student Admission Process (PPDB) Zonasi is an important stage for students and school institutions, and becomes an activity that must be carried out in schools, because this activity is the first step in a flow within the school. However, a situation and problems occurred in the Zoning New Student Admission (PPDB) in schools related to the Kurt Lewin Change Model, so that from the problem the researcher intended to conduct research on the implementation of Zoning PPDB according to the perspective of Kurt Lewin's Theory of Change which was seen through 3 stages of change, namely unfreeze, moving and refreeze. This type of research uses a qualitative approach where this research was carried out in the district of Timor Tengah Selatan in 2022, the data was obtained from the principal, teachers and administrative staff at SMA Negeri 1 Soe, the data was collected through interview, observation and documentation techniques, the data was then analyzed descriptively, The results were then analyzed in a descriptive way to explain the problem of the topic under study. The results of the study show (1) the situation of PPDB Zoning in SMA Negeri 1 Soe (2) PPDB Zoning problems in schools (3) The stage of change according to Kurt Lewin with 3 stages, namely unfreeze, refreezing, change that occur during PPDB implementation Zoning (4) The solution will be PPDB Zoning. and (5) Limitations of the Theory of Change according to Kurt Lewin.